Difference in recurrence frequencies of non-muscle-invasive-bladder tumors depending on optimal usage of intravesical immunotherapy of bacillus Calmette-Guérin - Milošević Radovan; Milović Novak; Aleksić Predrag; Lazić Miodrag; Cerović Snežana; Bančević Vladimir; Košević Branko; Marić Predrag; Spasić Aleksandar; Simić Dejan; Kovačević Božidar (Vojnosanitetski Pregled)
Background/Aim. The therapy with intravesical instillation of bacillus Calmette-Guérin (BCG) after transurethral resection (TUR) of the tumor is the gold standard of treatment of non-muscle invasive bladder cancer (NMIBC). The aim of this study was to compare the frequencies of reccurence between a group of patients submitted to TUR + BCG therapy (group I) and a group of patients submitted only to TUR (group II). Methods. The patients with NMIBC, a total of 899, treated in our Institution from January 1, 2007 to March, 2013, were included in this study and divided into two groups: group I and group II. These two groups were divided into three subgroups: solitary first diagnosed tumor ≤ 3 cm (SFDGT), solitary first diagnosed tumor > 3 cm and multiple first diagnosed tumors (MFDGT), and recedive tumors (RCT). Statistical analysis was performed by using χ2-test and Kolmogorov-Smirnov test. Results: In the group I a total of 133 cases had reccurence contrary to 75 in the group II, making a statistically highly significant difference. Analysis of recurrences through the subgroups revealed: in the group I SFDGT recurrence occured in 27 of the cases vs 9 cases in the group II; in the group I MFDGT recurrence occured in 49 of the cases vs 31 in the group II (p < 0.001), and finally, in the group I RCT recurrence occured in 57 cases vs 35 cases in the group II (p < 0.001). Conclusion. The obtained results indicate no difference in the frequency of reccurence between the group I and group II regarding SFDGT, but a very high significant difference regarding those with MFDGT and RCT. These results should be taken into consideration in everyday clinical practise.